2017
DOI: 10.1016/j.micron.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized nanoparticles enable tracking the rapid entry and release of doxorubicin in human pancreatic cancer cells

Abstract: Efficient drug delivery is critical to therapy. Using electron microscopy, X-ray, and light microscopy, we have characterized functionalized superparamagnetic iron oxide (SPIO) nanoparticles, and determined their ability for rapid entry and release of the cancer drug doxorubicin in human pancreatic cancer cells. Dextran-coated SPIO nanoparticle ferrofluid, functionalized with the red-autofluorescing doxorubicin and the green-fluorescent dye fluorescein isothiocyanate as a reporter, enables tracking the intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…We chose DOX as our drug of choice due to the ease of analysis by the virtue of its absorption and bright fluorescence properties, and our data support its good antitumor activity in line with other published studies. [35][36][37] We observed that all the tested cell types were capable of shedding of DOX-loaded Exos; however, the highest efficacy was observed for PCCs. This superior efficiency of PCCs can be attributed to the efficiency of cancer cells to pumpout drugs in a more effective way than other cell types.…”
Section: Discussionmentioning
confidence: 85%
“…We chose DOX as our drug of choice due to the ease of analysis by the virtue of its absorption and bright fluorescence properties, and our data support its good antitumor activity in line with other published studies. [35][36][37] We observed that all the tested cell types were capable of shedding of DOX-loaded Exos; however, the highest efficacy was observed for PCCs. This superior efficiency of PCCs can be attributed to the efficiency of cancer cells to pumpout drugs in a more effective way than other cell types.…”
Section: Discussionmentioning
confidence: 85%
“…A pancreatic cancer research shows that the chemotherapeutic adriamycin could be effectively transported and released in cancer cells by using superparamagnetic iron oxide NPs as carriers [18]. More inspiringly, a new administration route is discovered in brain tumor animal experiments.…”
Section: Evaluation Of Peg-mzf-np Gene Transfectionmentioning
confidence: 99%
“…Moreover, they can produce the heating effect and kill 95% cells [49]. A research on pancreatic cancer showed that chemotherapeutic DOX can be rapidly transferred and released in pancreatic cancer cells by using superparamagnetic iron oxide (SPIO) NPs as the vectors monitored under electron microscope, X-ray, and optical microscope [50]. As we all know, most chemotherapeutics cannot pass the blood brain barrier (BBB).…”
Section: Research On Magnetic Nps As Vectorsmentioning
confidence: 99%